2019
DOI: 10.33160/yam.2019.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Erythema Nodosum in a Child with a <i>SHOC2</i> Gene Mutation

Abstract: We report the case of a 6-year-old male who developed recurrent erythema nodosum (EN) at the age of 3 years. The patient exhibited hypertelorism, low-set ears, micrognathia, moderate intellectual disability, thin long fingers, loose anagen hair, and prominent palmoplantar wrinkles. A heterozygous single nucleotide variant in the SHOC2 gene (c.4 A > G, p.S2G) was identified. Patients with a SHOC2 mutation exhibit a unique combination of ectodermal abnormalities including darkly pigmented skin and loose anagen h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The SHOC2 gene affects proliferation, survival, and differentiation of epithelial stem cell-derived cells in hair follicles; however, the relationship between SHOC2 mutations and the other cutaneous pathologies seen specifically in NS/LAH remains unclear. 7 Increased signaling through RAS/MAPK contributes to oncogenesis, and solid tumors and hematologic malignancies are described in many of the RASopathies. 8 Patients with Costello syndrome can develop rhabdomyosarcoma, ganglioneuroblastoma, and bladder carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The SHOC2 gene affects proliferation, survival, and differentiation of epithelial stem cell-derived cells in hair follicles; however, the relationship between SHOC2 mutations and the other cutaneous pathologies seen specifically in NS/LAH remains unclear. 7 Increased signaling through RAS/MAPK contributes to oncogenesis, and solid tumors and hematologic malignancies are described in many of the RASopathies. 8 Patients with Costello syndrome can develop rhabdomyosarcoma, ganglioneuroblastoma, and bladder carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient's brain imaging findings, although the third and lateral ventricles dilatation and focal cortical anomaly in the right cerebellar hemisphere were reported previously, ectopic neurohypophysis was a novel finding. Autoimmune disorders including systemic lupus erythematosus (SLE) and erythema nodosum have been reported among patients among RASopathies, especially in SHOC2 pathogenic variants (Alanay, Balci, & Ozen, 2004;Okazaki et al, 2019;Simsek-Kiper et al, 2013;Uehara, Hosogaya, Matsuo, & Kosaki, 2018). However, although the underlying mechanism cannot be fully explained, it is suggested that this coexistence of such autoinflammatory diseases with RAsopathy in multiple patients is not random (Okazaki et al, 2019;Uehara et al, 2018).…”
Section: Discussionmentioning
confidence: 99%